Interactive effects of motor coordination and socioeconomic status on fundamental motor skills - Difi Deofsila; Syahrial Bakhtiar; Gusril Gusril; Yendrizal Yendrizal; Lucy Pratama Putri; Risky Syahputra (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the individual and combined effects of motor coordination and socioeconomic status on Fundamental Motor Skills (FMS) among elementary school students. A quantitative study using a 2 × 2 factorial design was conducted involving 72 students selected through purposive sampling from a population of 101 students at SDN 45 Bungo Pasang, Padang City. FMS were assessed using the Test of Gross Motor Development-2 (TGMD-2), motor coordination was measured using the (KTK), and socioeconomic status was classified based on parental socioeconomic data. Data were analyzed using descriptive statistics and Two-Way ANOVA. Significant differences were found between students with high and low motor coordination (p = 0.028) and between students with moderate and low socioeconomic status (p = 0.014). A significant interaction effect was also identified between motor coordination and socioeconomic status (p < 0.001). FMS development is influenced by both motor coordination and socioeconomic conditions, highlighting the importance of integrating individual motor competence and environmental support in physical education programs.